ASSESSMENT OF INFLUENCE OF RANGE FINDERS WITH THE IMPROVED CHARACTERISTICS ON THE ACCURACY OF GEOMETRICAL PARAMETERS CONTROL OF VEHICLES - A. M. Askhabov; E. S. Voevodin; V. A. Zeer; A. S. Kashura (Вестник СибАДИ, 2018)
Introduction. The purpose of the research is the determination of parameters and characteristics of the laser measuring systems providing decrease in errors of measurement of geometrical parameters of vehicles.The goal is achieved at the expense of the solution of the relevant task connected with the parameters research of the laser equipment and definition of requirements to accuracy (a passport error) of the laser range finders applied at geometrical parameters control of vehicles.Methods and materials. The algorithm of calculation of spatial coordinates of the car points and errors of their definition has been created and used for the research. In this case calculations of spatial provision of the point and its error have been reduced to definition and to the solution of the equations system of the second order in the MathCAD program environment. As the controlled and measured parameters at coordinates’ calculation of distances from laser measuring instruments to the studied car points were accepted.Results. As aresult, the mean square error of measurement of distance between control points significantly decreases at reduction of the passport error of laser range finders. At the size of the passport error of laser range finders equals 0,8 mm, the mean square error of measurement of distance between control points (from 0 to 3000 mm) equals 2,2-2,9 mm, and an error of definition of the control point is 1,5-1,9 mm.Discussion and conclusion. The conducted research demonstrates that it is necessary to compare the reached accuracy parameters at the set configuration of laser measuring system with the shown standard restrictions for an error of measurements. Therefore, further improvement of characteristics of accuracy of measuring systems is possible due to progressive decrease in an error of laser range finders as a result of their technical improvement.